2021
DOI: 10.9734/jpri/2021/v33i44b32661
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin: A Potential Multiple Targeted Drug Effectively Inhibits Diabetes Mellitus Protein Targets

Abstract: Background: Diabetes is a significant health problem that has reached worrisome proportions: almost half of the world's population now has diabetes. Diabetes mellitus, or diabetes, is a severe, long-term disease in which a person's blood glucose levels are elevated due to their body's inability to make any or enough insulin, or to properly utilise the insulin that it does produce. The chemicals extracted from medicinal plants were shown to be both safer and more bioactive than manufactured medicines. Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Thus, it prevents glucose optimization and then binding to glutamine-fructose-6-phosphate amido transferase (GFAT1), and Forkhead box protein O1 (FOX01), suggesting that it may help to avoid hyperglycemia. This shows that LUT is a potent inhibitor of type 2 diabetes mellitus [72]. During kidney hemorrhage, LUT significantly decreases MDA levels and increases SOD activity.…”
Section: Anti-diabetic Activitymentioning
confidence: 73%
“…Thus, it prevents glucose optimization and then binding to glutamine-fructose-6-phosphate amido transferase (GFAT1), and Forkhead box protein O1 (FOX01), suggesting that it may help to avoid hyperglycemia. This shows that LUT is a potent inhibitor of type 2 diabetes mellitus [72]. During kidney hemorrhage, LUT significantly decreases MDA levels and increases SOD activity.…”
Section: Anti-diabetic Activitymentioning
confidence: 73%
“…For instance, a recent study reported that A. lebbeck extracts showed potent inhibitory efficacies in contradiction of together wild-type and drug-resistant HIV-1 strains associated with infective endocarditis ( Kumar, 2021 , Gujjeti et al, 2014 , Mamidala et al, 2020 , Nair, 2013 ). Moreover, several bioactive compounds isolated from A. lebbeck , including Geraldone, Luteolin, and Isookanin, have been shown to possess anti-HIV-1 activities ( Chattopadhyay, 2013 , Nair, 2013 , Davella and Mamidala, 2021 , Kumar et al, 2020 ). The present study affords molecular understandings into the binding modes and interactions of A. lebbeck compounds with the DNA-p of HIV-1 RT.…”
Section: Discussionmentioning
confidence: 99%